GREEN INNOVATION IN INDONESIAN AGTECHS: EXPLORING THE ROLE OF INFORMAL CONTROLS - Ermelia , Sri; Ruchiyat, Endang; Matriadi , Faisal (Organisasi Kreatif Indonesia Emas, 2024)
Green innovation in Indonesia's agricultural sector offers great potential to increase productivity, environmental sustainability and farmer welfare. Informal controls, which include social norms, community networks, and the role of community leaders, play an important role in facilitating the adoption of green innovations among farmers. Social norms and values dominant in agricultural communities can influence farmers' decisions regarding the use of green technology. Community networks provide an important channel for information exchange and social support, while the role of community leaders can provide moral encouragement and inspiration for farmers to adopt green innovations. However, to increase the effectiveness of informal controls in supporting the adoption of green innovation, strong support from government, the private sector and community institutions is needed. The government can create a policy framework that supports the adoption of green innovation through clear regulations, fiscal incentives and subsidy programs. The private sector can play a role in developing innovative solutions and providing access to green technologies for farmers. Meanwhile, community institutions can provide social support, training, and advocacy to strengthen informal control within agricultural communities. With good cooperation between various stakeholders, we can create a conducive environment for the adoption of green technology in the agricultural sector, which will ultimately provide significant benefits for food security, environmental sustainability and the welfare of farmers in Indonesia.